Mixed Variety as a Way to Multilingualism and Multiethnicity of the Borderland (on the Example of Cieszyn Silesia in the Czech Republic) - Bogoczová, Irena (Slavistica Vilnensis, 2023)
The present paper discusses the linguistic situation in the Czech-Polish borderland, particularly in Zaolzie, which is the Czech part of Cieszyn Silesia. This region is inhabited by an autochthonous population comprising both Czech and Polish nationalities. Before moving on to the more important topics of the cultural and linguistic identity of the local Polish community, the author introduces Zaolzie from the geographical, social, political point of view. In addition to the majority Czech language and the standard Polish used in Polish minority schools, the Cieszyn dialect plays a significant role in local communication. Due to the unique political and social conditions in this region, a spoken mixed language called "po naszymu" has emerged. This language is not associated with any particular ethnic group, and it mitigates the differences between the various language codes while easing tensions between the two ethnic groups. The analysis of the spoken mixed language "po naszymu", carried out on the basis of extensive excerpts from authentic statements by Poles from Zaolzie in the "O naszych po naszymu" podcast, allows for several important conclusions: "po naszymu" speech does not have an unambiguous norm, which does not mean that it is the result of an accidental mixing of languages; it contains a lot of lexical Bohemisms; its phonetic and inflectional base is formed by the Polish dialect of West Cieszyn, nevertheless the users of "po naszymu" are aware of the incorrectness of their utterances in the sense of their incompatibility with the standard Polish language.
Keywords: dialect; Polish language; Czech language; Polish speech; Zaolzie